Design of Backpack Sprayer with Electrical Pumping System Using Quality Function Development Approach to Optimize the Agricultural Facility - Hernawa Maulana; Anna Nur Nazilah Chamim; Kunnu Purwanto; Ramadoni Syahputra; Teguh Iman Prasetyo (Journal of Electrical Technology UMY, 2018)
This paper presents an electric back sprayer based on the attributes required by sprayer users with the Quality Function Deployment (QFD) methodology by optimizing sprayers owned by farmers. In agriculture, the process of crop management and care and pest control is carried out routinely to obtain optimal results. The technical implementation of these efforts is carried out through soil and air media by spraying the plant organs. To keep the pressure and spray results stable, continuous pumping is required. This resulted in certainly more energy needed. Based on the results of research on farmers using a sprayer, the type that is widely used is the type of back sprayer. However, in the use of back type sprayers, farmers still experience problems. Problems encountered in using a back sprayer will be reviewed and overcome by developing a sprayer based on the wishes of the farmer. The design of the back sprayer using the Quality Function Deployment (QFD) method is more appropriate to be used in determining the attributes of the development of a back sprayer following the wishes of the fertilizer sprayer user. The resulting sprayer design is expected to be able to overcome the weaknesses in the back sprayer without having to procure a new sprayer, where the problem of the non-constant pressure level in pumping can be overcome.